A Time Series Analysis of Cancer-Related Information Seeking: Hints From the Health Information National Trends Survey (HINTS) 2003–2014. Issue 9 (1st September 2016) - Huerta, Timothy R.; Walker, Daniel M.; Johnson, Tyler; Ford, Eric W.
Abstract : Recent technological changes, such as the growth of the Internet, have made cancer information widely available. However, it remains unknown whether changes in access have resulted in concomitant changes in information seeking behavior. Previous work explored the cancer information seeking behaviors of the general population using the 2003 Health Information National Trends Survey (HINTS). This article aims to reproduce, replicate, and extend that existing analysis using the original dataset and five additional iterations of HINTS (2007, 2011, 2012, 2013, 2014). This approach builds on the earlier work by quantifying the magnitude of change in information seeking behaviors. Bivariate comparison of the 2003 and 2014 data revealed very similar results; however, the multivariate model including all years of data indicated differences between the original and extended models: individuals age 65 and older were no longer less likely to seek cancer information than the 18–35 reference population, and Hispanics were also no longer less likely to be cancer information seekers. The results of our analysis indicate an overall shift in cancer information seeking behaviors and also illuminate the impact of increased Internet usage over the past decade, suggesting specific demographic groups that may benefit from cancer information seeking encouragement.